Chemical compositional changes in archaeological human bones due to diagenesis: Type of bone vs soil environment - López-Costas, Olalla; Lantes-Suárez, Óscar; Martínez Cortizas, Antonio (Journal of archaeological science, 2016)
Diagenesis in human remains is a subject of growing interest due to the increase in bone chemical studies to reconstruct pre- and post-mortem features in archaeological and forensic sciences. The efforts made during the last decades have solidified our understanding of diagenetic processes; however, their high complexity demands more research to address them empirically, specifically considering factors such as types of soil substratum and skeletal element. In this work, a geochemical study of human remains from the archaeological site of A Lanzada (NW Spain) is performed to understand diagenesis (i.e. chemical alteration) and life environmental exposure. Three types of bone (thoracic, long and cranial) from 30 skeletons of two periods (9 Roman, 21 post-Roman) were analysed by X-ray fluorescence. Bones were recovered from burials located in slightly alkaline (Haplic Arenosol (calcaric)) and acidic (Cambic Umbrisol (humic)) soils. Principal components analysis was applied to extract the main chemical signatures, and analysis of variance to determine the influence of different factors. Bone composition was characterized by four chemical signals related to: i) alteration of bone bioapatite; ii) metal sorption from the soil solution; iii) presence of fine (silt–clay) soil particles; and iv) lead incorporation. Thoracic bones were found to be more sensitive to diagenesis and the burial environment; long bones and crania presented a similar response. Skeletons buried in the acidic soil were significantly poorly preserved. Lead content was higher in bones of the Roman period, which seems to be related to pre-mortem conditions. Previous investigations on palaeopollution in NW Spain enable us to hypothesize that Roman individuals may have been subjected to a high exposure of Pb due to elevated atmospheric metal contamination. •Bones (3 types) of 2 periods and buried in 2 soil environments were analysed by XRF.•Chemical alteration is the main diagenetic process underwent by bone.•Thoracic bones were more affected than long or cranial ones, especially in the acidic soil.•Metal sorption and fine particles attachment were identified as secondary processes.•Lead was probably incorporated pre-mortem, showing higher contents in Roman skeletons.